Analisis Laporan Keuangan Bank terhadap Return Saham pada Bank Umum Swasta Nasional Devisa Periode 2011—2015 - Erric Wijaya; Muhammad Reyhan (STIE Indonesia Banking School, 2017)
The purpose of this study was to determine and analyze the effect of bank financial report using variable Loan to Deposit Ratio (LDR), Capital Adequacy Ratio (CAR), Return On Asset (ROA), and Operating Income Operating Expenses (OIOE/BOPO) toward a stock return in a conventional bank. The sample selection using purposive sampling method and a sample of this research are as many as 18 national private commercial bank foreign exchange in Indonesia. Data obtained from secondary data in annual reports of a bank in Indonesia Stock Exchange sites. The analysis technique used in this research is multiple regression analysis. The hypothesis in this study was based on previous studies and various other supporting theories. The results of this study indicate that the loan to deposit ratio (LDR) positively effect on stock return, capital adequacy ratio (CAR) no significant effect on stock return, return on asset (ROA) positively effect on stock return. While Operating Income Operating Expenses variable removed for affected Multikolinierity.